530. LAPAROSCOPIC REPAIR OF ESOPHAGEAL PERFORATION. (24th September 2022) - Lim, Xin Yan; Lee, June
Abstract: Esophageal perforation is associated with high morbidity and mortality. Early detection and treatment are vital as delays substantially increases mortality risk. Management options include surgical repair, drainage, diversion, endoscopic stenting/clipping and conservative management. Treatment of choice depends on etiology, location and duration between perforation and detection. Surgical repair remains as the mainstay of treatment if perforation is diagnosed <24 hours. However, for perforation detected > 24 hours, management is controversial with many advocating non-operative therapy. We present the case of a 68-year-old gentleman who underwent laparoscopic repair of an iatrogenic esophageal perforation. He first presented with dysphagia secondary to esophageal peptic stricture, initial biopsy showing no signs of malignancy. Patient underwent serial endoscopic dilatations, which was complicated with an iatrogenic esophageal perforation during his second dilatation. He underwent an urgent laparoscopic distal esophagectomy and proximal gastrectomy to resect the diseased part of the esophagus- intraoperatively noted a 1cm perforation over distal esophagus. A double tract reconstruction was then performed to restore continuity of the gastrointestinal tract and reduce gastric reflux to the esophagus. Patient was started on clear feeds on post-operative day 1 with gradual escalation of feeding to soft diet on post-operative day 4. His post-operative recovery was largely uneventful and he was discharged on post-operative day 7. Histological examination however returned as a pT3N1a moderately differentiated oesophageal squamous cell carcinoma. A PET-CT scan and repeat gastroscopy done showed no residual or distant disease. His condition was discussed in multidisciplinary meeting and patient then underwent definitive chemotherapy and radiotherapy. Although early recognition, detection and treatment of esophageal perforation are important for good outcomes, delays in diagnosis and treatment are usually due to rarity of this condition and lack of familiarity with management. Our video aims to showcase the surgical repair of a distal esophageal perforation and reconstruction in a minimally invasive fashion. Aim of surgery should include repair of perforation, cleaning up contamination, restoring gastrointestinal continuity and resolution of any underlying etiology.